Prevention of iron deficiency anemia in pregnancy and lactation - A. Yu. Romanov (Медицинский совет, 2020)
The article is devoted to the issues of prevention and choice of therapy strategy for iron deficiency anemia in pregnant women. Iron deficiency anemia is a frequent complication during pregnancy and in the postnatal period. According to the World Health Organization (WHO), the frequency of anemia in pregnant women exceeds 40% and can reach 65% in developing countries. More than half of all cases of anemia during pregnancy are directly related to iron deficiency (ID), which can be as high as 80% or more during pregnancy. This indicates that existing iron reserves out of pregnancy are inadequate to compensate for the increasing need for iron intake during pregnancy. According to domestic authors, the vast majority of women have some kind of iron deficiency by the end of pregnancy, and some of them had a latent iron deficiency even before pregnancy. The development of anemia is preceded by sublatent and latent forms of iron deficiency associated with increased iron demand during gestation. The issues of early diagnostics of preclinical forms of iron deficiency with subsequent correction of this element insufficiency, which allows avoiding undesirable phenomena related to the development of anemia, remain particularly relevant. The prevention of iron deficiency anemia should be complex and individual, and the choice of a drug to compensate for iron deficiency should be based on high bioavailability of the drug with minimal side effects. According to available data, oral administration of bior trivalent iron preparations is not sufficient for the treatment of moderate to severe anemia. In this case, the administration of iron sulphate preparations should be combined with the prescription of prolonged or recombinant erythropoietin with a transition to intravenous administration of iron preparations.